The Role of Democratic Parenting in Developing the Social Intelligence of Three Year-Old Children - Aura Ayu Devani; Fitri Ayu Fatmawati; Ayunda Sayyidatul Ifadah (Indonesian Journal of Early Childhood Educational Research (IJECER), 2025)
This study aims to examine how democratic parenting contributes to the development of social intelligence in three-year-old children by identifying the specific strategies employed by parents in daily interactions. Using a qualitative case study approach involving one family, data were collected through observation, in-depth interviews, and documentation. The findings show that democratic parenting is reflected through structured practices such as offering autonomy through choices, fostering prosocial behavior, engaging in dialogic communication, and utilizing play as a medium for guidance. These strategies effectively nurture children’s confidence, empathy, and foundational social skills. The study concludes that democratic parenting is not a permissive approach but an intentional and active form of guidance that consistently strengthens the child’s social intelligence. The results highlight the importance of consciously applying these practices to optimize early social development.